2019
DOI: 10.3389/fpsyt.2019.00694
|View full text |Cite
|
Sign up to set email alerts
|

Significant Decrease in Hippocampus and Amygdala Mean Diffusivity in Treatment-Resistant Depression Patients Who Respond to Electroconvulsive Therapy

Abstract: Introduction: The hippocampus plays a key role in depressive disorder, and the amygdala is involved in depressive disorder through the key role that it plays in emotional regulation. Electroconvulsive therapy (ECT) may alter the microstructure of these two regions. Since mean diffusivity (MD), is known to be an indirect marker of microstructural integrity and can be derived from diffusion tensor imaging (DTI) scans, we aim to test the hypothesis that treatment-resistant depression (TRD) patients undergoing bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 46 publications
5
21
0
Order By: Relevance
“…The decrease in MD, which is in line with recent studies looking into the effects of ECT on DTI measurements [46,47], indicates that the formation of edema is a very unlikely explanation for the volumetric increase in the hippocampus. As vasogenic edema would increase the water content in the extracellular space, this could be reflected in an increase in MD or at least a no detectable change in MD (depending on the sensitivity of the IVIM framework and IVIM scan), as opposed to a decrease in MD.…”
Section: Discussionsupporting
confidence: 88%
“…The decrease in MD, which is in line with recent studies looking into the effects of ECT on DTI measurements [46,47], indicates that the formation of edema is a very unlikely explanation for the volumetric increase in the hippocampus. As vasogenic edema would increase the water content in the extracellular space, this could be reflected in an increase in MD or at least a no detectable change in MD (depending on the sensitivity of the IVIM framework and IVIM scan), as opposed to a decrease in MD.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, mean diffusivity, a measure of the diffusion of water molecules in the brain, is assessed in diffusion tensor imaging to make statements about the microstructural integrity where increased values are hypothesized to reflect a low restriction of water molecules (e.g. due to cells) and thereby a degeneration of microstructural integrity; several investigations showed a decrease in mean diffusivity after a course of ECT favoring neuroplasticity as underlying mechanism over vasogenic edema that would be accompanied by an increased mean diffusivity due to accumulating extracellular fluids [18,50,74]. Still, an intracellular fluid/ion shift (cell swelling) induced by the seizure cannot be ruled out and would explain the reversibility of the volumetric effects [75].…”
Section: Discussionmentioning
confidence: 99%
“…DTI studies of the hippocampus after ECT found an MD decrease, which does not support the vasogenic edema. 54,55 Further, a recent ultra-high field (7 Tesla) MRI study, which was designed to test the presence of hippocampal edema after ECT, did not find any indication of it. 56 Cytotoxic edema is also a possibility.…”
Section: Other Mechanismsmentioning
confidence: 99%